A new approach toward understanding the relationship between tinnitus and stress - Elarbed, Asma Ali K. (2022)
This thesis examined the relationship between tinnitus and stress. Chapter 1 provides an overview of tinnitus and stress in terms of definitions, terminologies, mechanism, classification, assessment, and management. Chapter 2 describes the similarities between tinnitus and stress. It is divided into three sections. In the first section, I explain how both tinnitus and stress are associated with changes in brain function and structure, are associated with several diseases, and affect cognition. The second section summarises the findings of a scoping review of research on tinnitus and stress. It revealed discrepancies in the findings and limitations in the methodologies of reviewed studies. Cortisol was commonly studied. Thus, the third section describes the methods and findings of studies that assessed cortisol in tinnitus. The findings in this chapter informed the empirical studies described in the remaining chapters.